Penerapan Intradialytic Stretching Exercise pada Dewasa Muda yang Menjalani Hemodialisis dengan Kram Otot: Laporan Kasus - Dhea Natashia; Erwan Setiyono; Rizki Nugraha Agung; Siti Nafisah; Laela Nur Adzmi; Siti Aisyah Afifah (Jurnal Kesehatan Holistic, 2026)
Background: Intradialytic muscle cramps are common complications experienced by patients with Chronic Kidney Disease (CKD) undergoing hemodialysis and may interfere with patient comfort and dialysis effectiveness. Intradialytic stretching exercise is a non-pharmacological nursing intervention that may help reduce these symptoms. Case Presentation: Two young adult patients with CKD undergoing routine hemodialysis at Jakarta Islamic Hospital, Cempaka Putih, experienced recurrent lower-extremity muscle cramps during hemodialysis sessions, particularly during the final hours of treatment. The first patient was 21 years old with an initial pain score of 4, while the second patient was 22 years old with an initial pain score of 5 based on the Numeric Rating Scale (NRS). Intervention and Outcomes: Both patients received intradialytic stretching exercises during two hemodialysis sessions, including ankle dorsiflexion movements and stretching of the gastrocnemius, soleus, hamstring, and quadriceps muscles. Following the intervention, both patients demonstrated reduced pain intensity and fewer muscle cramp complaints. The patients also appeared more relaxed and comfortable during hemodialysis sessions. Conclusion: Intradialytic stretching exercise may serve as an effective non-pharmacological nursing intervention to help reduce muscle cramp pain in patients with CKD undergoing hemodialysis. This intervention is simple to implement and may be considered as part of routine nursing care in hemodialysis units. Keywords: Chronic Kidney Disease; Hemodialysis; Intradialytic Stretching Exercise; Muscle Cramps; Nursing Intervention